Geopolymer-bamboo composite – A novel sustainable construction material - Ribeiro, Ruy A. Sá; Sá Ribeiro, Marilene G.; Sankar, Kaushik; Kriven, Waltraud M. (Construction and Building Materials, 2016)
In the pursuit of sustainable construction, regional natural materials can be used as a base for geopolymer processing. For higher strength achievement, this study uses mixed potassium-sodium polysialate siloxo-type geopolymer reinforced with bamboo fibers and strips. The composite geopolymer reinforced with bamboo fibers was used as a binder for the bamboo strips. Geopolymer was synthesized using metakaolin produced from kaolinite extracted from Amazonian soil, and microscopically compared to a commercial, highly reactive, Metamax metakaolin-based geopolymer. Amazonian kaolin was converted into metakaolin by calcination up to 700 °C. X-ray diffraction (XRD) analysis showed the resulting amorphous metakaolin to be 76% pure, with 24% crystalline quartz impurity. Four-point flexural and compressive strength testing of the geopolymer were carried out according to ASTM standards C1341-13 and C1424-10. Scanning electron microscopy (SEM) was used to investigate the microstructure and the interface. In addition, XRD was used to confirm the formation of geopolymer. Amazonian metakaolin geopolymer reinforced with bamboo is a potential green sustainable construction material with compressive strength ranging from: 23–38 MPa for micro bamboo fibers alkali treated (BF1A), 23–25 MPa for short BF alkali treated (BF4A), and 25–29 MPa for short BF water treated (BF4W). Flexural strength values for geopolymer reinforced with bamboo fibers ranged from: 4–8 MPa for BF1A, 7–8 MPa for BF4W, and reached 21–30 MPa for mixed BF1A and bamboo strip reinforcements. © 2016 Elsevier Ltd
Keywords: Bamboo; Bending Strength; Compressive Strength; Fibers; Inorganic Polymers; Kaolinite; Reinforced Plastics; Reinforcement; Microscopy, Electron, Scanning; Standards; Sustainable Development; Water Treatment; X Ray Diffraction Analysis; Amazon; Amorphous Metakaolin; Compressive Strength Testing; Crystalline Quartz; Geopolymer; Geopolymer Composites; Metakaolins; Sustainable Construction; Geopolymers; Bamboo; Bend Strength; Composites; Compression Strength